Foot disorders in children. Issue 1 (January 2017) - Chytas, Anastasios; Morakis, Emmanouil
Abstract: There is a wide range of foot disorders and deformities in children. While most of them are benign, some of the foot deformities may require operative intervention and/or a prolonged period of treatment. We will discuss the most common of these disorders: clubfoot, congenital vertical talus, calcaneovalgus deformity, metatarsus adductus, flexible flatfoot, tarsal coalitions and cavus foot.